Effects of seed vigor on growth and grain yield of maize - Ghassemi-Golezani, Kazem; Dalil, Bahareh (Plant Breeding and Seed Science, 2014)
Reduction in seed vigor is a consequence of seed aging which may influence field performance of crops. Thus, a field study was conducted as RCB design with 6 replicates to evaluate the effects of seed vigor on maize (cv. Ksc 301) growth and yield. A sub-sample of maize seeds was kept as control and two other sub-samples were artificially aged for 9 and 12 days. So, three seed lots (V1, V2 and V3), with different vigor were provided and sown in the field. Mean emergence time significantly increased, but mean emergence percentage decreased as seed vigor increased. The lowest leaf area index (LAI), dry matter accumulation (DMA) and crop growth rate (CGR) were obtained for plants from the lowest vigor seed lot (V3). At the later stages of growth, the highest relative growth rate (RGR) was recorded for V1 plants, followed by V2 and V3 plants. Poor stand establishment and growth of plants from V2 and V3 seed lots led to yield loss by 23.7 % and 41.5 %, respectively. These results showed that production and cultivation of high vigor seeds are necessary to ensure satisfactory field performance of maize.